MODELING THE EXTERNAL ENVIRONMENT DYNAMICS OF REAL ESTATE PROJECT: Array - Kramarenko, V.; Dolgova, N. (Municipal economy of cities. Series: «Economy science», 2021)
The article examined the problem of the determination of exogenous factors of investment and real estate projects. During the investigation, were highlighted the construction project external environment factors. The expert external stakeholders' impact analysis was performed on the material resources management process using hierarchy analysis. Determination of the cause-effect relationship between the main parameters of the project as of the cost of production, price of the dwelling, the rental rate on the housing market, duration of the project, and influence of the interests of external stakeholders was performed by the hierarchy analysis process. Was solved the multicriteria problem of determining the most significant project parameter and ranking stakeholders according to the degree of influence on the project parameters. The most crucial parameter in the management of resources of the construction project was determined as the construction cost. The construction prime cost trend availability check was performed by the Foster-Stewart method. Collection and processing of statistical data have been carried out. Basing on that data, we conducted building and analysis of the model of multiple regression of construction and installation prime cost of residential property construction, considering exogenous factors. The exogenous factors were considered as the inferred numerical characteristics of external stakeholders' influence. The resulting regression model parameters analysis revealed exogenous factors with the most significant efficiency impact on resource management. The research defines the necessity of using mathematical apparatus for processing qualitative and quantitative information about the external environment of a real estate object dynamics as a component of information technologies for material resources management at the strategic and operational levels.